The formation of surface multilayers at the air-water interface from sodium polyethylene glycol monoalkyl ether sulfate/AlCl(3) solutions: the role of the size of the polyethylene oxide group. - Xu, H; Penfold, J; Thomas, R; Petkov, J; Tucker, I; Webster, J (2013)
Neutron reflectivity, NR, and surface tension, ST, have been used to study the surface adsorption properties at the air-water interface of the anionic surfactant sodium polyethylene glycol monododecyl ether sulfate (sodium lauryl ether sulfate, SLES) in the presence of Al(3+) multivalent counterions, by the addition of AlCl3. In the absence of AlCl3 and at low AlCl3 concentrations monolayer adsorption is observed. With increasing AlCl3 concentration, surface multilayer formation is observed, driven by SLES/Al(3+) complex formation. The onset of multilayer formation occurs initially as a single bilayer or a multilayer structure with a limited number of bilayers, N, ≤3, and ultimately at higher AlCl3 concentrations N is large, >20. The evolution in the surface structure is determined by the surfactant and AlCl3 concentrations, and the size of the polyethylene oxide group in the different SLES surfactants studied. From the NR data, approximate surface phase diagrams are constructed, and the evolution of the surface structure with surfactant and electrolyte concentration is shown to be dependent on the size of the polyethylene oxide group. As the polyethylene oxide group increases in size the multilayer formation requires increasingly higher surfactant and AlCl3 concentrations to promote the formation. This is attributed to the increased steric hindrance of the polyethylene oxide group disrupting SLES/Al(3+) complex formation.